A novel method for strict intranasal delivery of non-replicating RSV vaccines in cotton rats and non-human primates. Issue 20 (11th May 2018) - Citron, Michael P.; Patel, Manishkumar; Purcell, Mona; Lin, Shu-An; Rubins, Daniel J.; McQuade, Paul; Callahan, Cheryl; Gleason, Alexa; Petrescu, Ioan; Knapp, Walter; Orekie, Chinedu; Chamarthy, Sai; et al.
Highlights: The importance of immunization method for each preclinical species. Traditional immunization methods distribute incola in both URT and LRT. Immune responses can differ depending on biodistribution. Dosing preclinical species inaccurately can lead to exaggerated results. Used imaging to define a method for strict intranasal immunization. Abstract: Respiratory syncytial virus (RSV) is the most common viral cause of bronchiolitis and pneumonia in children twelve months of age or younger and a significant cause of lower respiratory disease in older adults. As various clinical and preclinical candidates advance, cotton rats ( Sigmodon hispidus ) and non-human primates (NHP) continue to play a valuable role in RSV vaccine development, since both animals are semi-permissive to human RSV (HRSV). However, appropriate utilization of the models is critical to avoid mis-interpretation of the preclinical findings. Using a multimodality imaging approach; a fluorescence based optical imaging technique for the cotton rat and a nuclear medicine based positron emission tomography (PET) imaging technique for monkeys, we demonstrate that many common practices for intranasal immunization in both species result in inoculum delivery to the lower respiratory tract, which can result in poor translation of outcomes from the preclinical to the clinical setting. Using these technologies we define a method to limit the distribution of intranasally administered vaccines solely to the upper airway of each species, which includes volume restrictions in combination with injectable anesthesia. We show using our newly defined methods for strict intranasal immunization that these methods impact the immune responses and efficacy observed when compared to vaccination methods resulting in distribution to both the upper and lower respiratory tracts. These data emphasize the importance of well-characterized immunization methods in the preclinical assessment of intranasally delivered vaccine candidates.